Pembangunan Kamera Pemantau Ruang Teknisi Sekolah Menengah Kejuruan Negeri 1 Karanganyar - Suyatno .; Dimas Sasongko . (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2017)
Abstrack: Tekinisi space Vocational Height School 1 Karanganyar (SMK Negeri 1 Karanganyar) is a storage area technician tools and backup storage komputer peripherals. Security in space engineers still SMK Negeri 1 Karanganyar still a problem. The absence of security support technology to one of the obstacles. The presence of surveillance cameras is a need to support the security sistem technicians space Vocational Height School 1 Karanganyar. Surveillance camera in question is a surveillance camera that can be seen ol line using either a komputer or mobile phone. The camera can record all the events going on in the tech space. Recordings are stored on a komputer hard drive in the form of video that can be viewed or played back when needed. With the monitor on the camera dibangunya line is expected to assist in monitoring the safety of the technician room Vocational Height School 1 Karanganyar. In this study the authors used the following research methods of observation, interviews, analysis, library research, design, preparation, lan development, testing, implementation. Abstraksi: Ruang teknisi Sekolah Menengah Kejuruan Negeri 1 Karanganyar (SMK Negeri 1 Karanganyar) merupakan tempat penyimpanan alat-alat teknisi dan tempat penyimpanan cadangan peripheral komputer. Keamanan pada ruang teknisi SMK Negeri 1 Karanganyar masih menjadi masalah. Belum adanya teknologi pendukung keamanan menjadi salah satu kendala. Adanya kamera pengawas merupakan sebuah kebutuhan guna menunjang sistem keamanan ruang teknisi SMK Negeri 1 Karanganyar. Kamera pengawas yang dimaksud adalah kamera pengawas yang bisa dilihat secara baik menggunakan komputer dan dapat merekam semua kejadian yang terjadi di dalam ruang teknisi. Hasil rekaman kamera disimpan pada sebuah hardisk komputer dalam bentuk video yang bisa dilihat ataupun diputar kembali bila dibutuhkan. Dengan dibangunya kamera pemantau ini diharapkan dapat membantu pemantauan keamanan pada ruang teknisi SMK Negeri 1 karanganyar. Dalam penelitian ini penulis menggunakan metode penelitian sebagai berikut observasi, wawancara, analisis, studi pustaka, perancangan, persiapan, pembangunan lan, testing, implementasi.Kata Kunci : Kamera pengawas, Ruang Teknisi, Keamanan